Pengaruh Likuiditas dan Solvabilitas Terhadap Perubahan Laba Pada Perusahaan Manufaktur (Studi Empiris Pada Sektor Aneka Industri) - Nina Marlina; Yudiana Yudiana (Komunitas Dosen Indonesia, 2024)
Liquidity ratios and solvency ratios are measurements to determine the extent of changes in profits in a company. This research was conducted in manufacturing companies in various industrial sectors that are registered on the IDX. In a research, there must be a research method in it, the method used in this research is the liquidity ratio to measure the Current Ratio (current assets) and the Debt to Equity Ratio which is used to determine the comparison between the recapitulation of company debt and company capital, the technique used to take samples namely purposive sampling. Hypothesis testing in this research was carried out using multiple linear regression analysis techniques. The conclusion that can be drawn from the results of this research is that the Current Ratio score influences changes in profit as evidenced by a significant value of 0.008 < 0.05. Meanwhile, the Debt to Equity Ratio has a value of 0.055>0.05, which means that the debt to equity ratio has no significant impact on changes in profits. Simultaneously, the current ratio and debt to equity ratio have a significant impact on changes in profit.